Polaronic metal state at the LaAlO3/SrTiO3 interface - C. Cancellieri (Nature Portfolio, 2016)
Polarons are quasiparticles formed when an electron strongly couples to the lattice vibrations, or phonons, in a crystalline material. Here, the authors use soft-X-ray angle-resolved photoelectron spectroscopy to identify signatures of metal polarons at the interface between two oxide materials.